Multivariate Analysis Of Infertility Risk Factors In Fertile Age Couples - Syahridayanti Syahridayanti; Surtikanti Surtikanti; Marwan Ahmad Ganoko; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
Infertility is a reproductive health problem that impacts the biological, psychological, and social aspects of couples of childbearing age (PUS). Various factors such as age, body mass index (BMI), history of infection, hormonal disorders, and lifestyle are suspected to play a role in the occurrence of infertility. This study aims to analyze the risk factors for infertility in couples of childbearing age using a multivariate approach. The study used a case-control design with a sample of 120 respondents (60 infertility cases and 60 fertile controls). Data were collected through structured interviews and medical record reviews. Analysis was performed using multiple logistic regression to determine the dominant risk factors. The results showed that the wife's age ≥35 years (OR=3.8; p=0.002), a history of reproductive tract infections (OR=4.5; p=0.001), an abnormal BMI (OR=2.9; p=0.010), and the husband's smoking habit (OR=3.2; p=0.005) were significant risk factors for infertility. The dominant factor was a history of reproductive tract infections. It is concluded that infertility is multifactorial and requires a comprehensive approach in its prevention and treatment.